Diretrizes curriculares nacionais do Ensino Religioso: uma proposta fundamentada na Ciência da Religião = National curriculum guidelines for Religious Education : a proposal based on the Science of Religion - Costa, Matheus Oliva da (Ciencias sociales y religión, 2015)
The Religious Education is the unique school discipline that does not have an official PCN by MEC. Aiming to fill this gap is that we present here our RE national curricular parameter proposal. We use a clear scientific reference, the Scientific Study of Religion / Religious Studies, which serves as a parameter for didactic transpositions to RE. We present a brief explanation and then we present the curricular structure to the ER in the form of a systematic framework. We propose that this is a national framework for this discipline and can will serve as a model for a future official PCN. Because beyond content also we showed object of study objective and methodology for this area.